Suatu pengantar pelayaran perairan daratan / Iskandar Abubakar, Herdjan Kenasin, dan B. Barzach - ISKANDAR Abubakar; HERDJAN Kenasin; BARZACH, B. (Raja Grafindo Persada, 2013)
xvi, 224 hlm. : ilus. ; 20,5 cm.